Timeline for An-Nisa’ based on occasions of revelation - Ali, Rashid Issack (Journal of Islamic Sciences, 2023)
The purpose of this study was to precisely date suratul An-nisa’ using reports of occasions of revelation (asbabul nuzul), and to tackle this problem, the study adopted two methods: track and examine all the asbab accounts related to An-nisa’ and date the historical events yielded by the asbab using Sira works.The study employed a case study method to collect data and historically analyze An-nisa’. The findings of the study reveal: 1) that five battles of the prophet are crucial to dating of An-nisa precisely, namely: Uhud, Badr mawid, Dhat al-Riqa, Al-Muraysi' and Khandaq;  2) that An-nisa has two distinct periods of descent: a core period of 15 months and a later minor period, occurring around year 10 in which a few verses descended. The core period started from the middle of year 4 and closed at the start of the ninth month of year 5 of Hijri calendar, constituting the critical time period for An-nisa’ during which bulk of its verses were gradually revealed.
Keywords: Surat Al-Nisa; reasons for the revelation of the Qur’an; chronology; the revelation of the Qur’an